Addressing the Health Implications of Heat Waves: Urgent Actions for Protection and Resilience - Rafif Naufi Waskitha Hapsari; Heru Santoso Wahito Nugroho; Abdullah Al Mamun (Knowledge Dynamics, 2024)
Not mandatory